Emotional crisis in a naturalistic context: characterizing outpatient profiles and treatment effectiveness - Zanello, Adriano (BMC Psychiatry, 2017)
BACKGROUND: Crisis happens daily yet its understanding is often limited, even in the field of psychiatry. Indeed, a challenge is to assess the potential for change of patients so as to offer appropriate therapeutic interventions and enhance treatment program efficacy. This naturalistic study aimed to identify the socio-demographical characteristics and clinical profiles at admission of patients referred to a specialized Crisis Intervention Center (CIC) and to examine the effectiveness of the intervention. METHOD: The sample was composed of 352 adult outpatients recruited among the referrals to the CIC. Assessment completed at admission and at discharge examined psychiatric symptoms, defense mechanisms, recovery styles and global functioning. The crisis intervention consisted in a psychodynamically oriented multimodal approach associated with medication. RESULTS: Regarding the clinical profiles at intake, patients were middle-aged (M = 38.56, SD = 10.91), with a higher proportion of women (62.22%). They were addressed to the CIC because they had attempted to commit suicide or had suicidal ideation or presented depressed mood related to interpersonal difficulties. No statistical differences were found between patients dropping out (n = 215) and those attending the crisis intervention (n = 137). Crisis intervention demonstrated a beneficial effect (p < 0.01) on almost all variables, with Effect Sizes (ES) ranging from small to large (0.12 < ES < 0.75; median = 0.49). However, the Reliable Change Index indicated that most of the issues fall into the undetermined category (range 41.46 to 96.35%; median = 66.20%). CONCLUSIONS: This study establishes the profile of patients referred to the CIC and shows that more than half of the patients dropped out from the crisis intervention before completion. Our findings suggest that people presenting an emotional crisis benefit from crisis intervention. However, given methodological constraints, these results need to be considered with caution. Moreover, the clinical significance of the improvements is not confirmed. Thus, the effectiveness of crisis intervention in naturalistic context is not fully determined and should be more rigorously studied in future research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-017-1293-3) contains supplementary material, which is available to authorized users.